Розробка тренажеру зору - Костін, Д. О.; Тимкович, М. Ю. (ХНУРЕ, 2020)
At this stage of the development of a civilized society, digital technologies have reliably strengthened in most areas of the life of a modern person. However, frequent overloading of the visual organs can lead to various kinds of diseases. Thus, creating for modern biomedical engineering in the field of ophthalmology is the need to develop many methods for the diagnosis and treatment of organs of vision.
Keywords: тренажер; зір; лазерний промінь; пристрій проєктування